2016
DOI: 10.1002/ece3.2210
|View full text |Cite
|
Sign up to set email alerts
|

Carbon cycling in temperate grassland under elevated temperature

Abstract: An increase in mean soil surface temperature has been observed over the last century, and it is predicted to further increase in the future. The effect of increased temperature on ecosystem carbon fluxes in a permanent temperate grassland was studied in a long‐term (6 years) field experiment, using multiple temperature increments induced by IR lamps. Ecosystem respiration (R‐eco) and net ecosystem exchange (NEE) were measured and modeled by a modified Lloyd and Taylor model including a soil moisture component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…( Delmotte et al, 2009 ). Jansen-Willems et al (2016) showed, that the plant biomass increased in T plots, which indicated changes of the plant physiology and morphology. A first insight into metabolome profiles of G. album leaves of C and T plots indicated significant differences among leave metabolomes (unpublished data).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…( Delmotte et al, 2009 ). Jansen-Willems et al (2016) showed, that the plant biomass increased in T plots, which indicated changes of the plant physiology and morphology. A first insight into metabolome profiles of G. album leaves of C and T plots indicated significant differences among leave metabolomes (unpublished data).…”
Section: Discussionmentioning
confidence: 92%
“…Global warming is an ongoing climate change effect and will lead to an increase of the mean global air temperature by 2–3°C until 2050 as predicted by the Intergovernmental Panel on Climate Change ( IPCC, 2013 ). Elevated surface temperature can affect plants and their symbiotic microbiota (the plant holobiont; Margulis, 1993 ; Vandenkoornhuyse et al, 2015 ) by influencing plant growth, health, and yield ( Wu et al, 2011 ; Jansen-Willems et al, 2016 ). An important plant-associated habitat colonized by specific bacterial communities is the phyllosphere, the aerial part of plants dominated by leaves ( Vorholt, 2012 ; Bringel and Couée, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible explanation for the in situ reduction of denitrification could be the altered field soil moisture content. While during the incubation, soil moisture was purposely kept constant (WFPS of 64 %); in the field, however, moisture conditions were affected by the heating treatment, leading to generally drier, and thus more aerated, conditions in the heated plots (Jansen-Willems et al, 2016). Under low WFPS, nitrification is predominantly responsible for N 2 O efflux (Bollmann and Conrad, 1998;Bateman and Baggs, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The temperature treatments (including any moisture effect) are referred to as T control , T 1 , T 2 and T 3 , respectively. The infrared heaters were installed at different heights to create the different temperature elevations (Jansen-Willems et al, 2016).…”
Section: Site Description and Field Treatmentmentioning
confidence: 99%